A Marxist Examination of Kyuri’s Alienation under K-beauty Standards in If I Had Your Face - Raissa Belva Ardianti; Diana Budi Darma (Journal of English Language and Education, 2026)
This study examines how K-beauty standards function as a form of ideological control and how they produce alienation in the character Kyuri in If I Had Your Face by Frances Cha. Although previous studies have discussed K-beauty and gender representation, limited research has explored K-beauty standards through a Marxist perspective, particularly in relation to ideology and alienation in literary works. Using qualitative textual analysis and a Marxist literary framework, this study focuses on the concepts of ideology, false consciousness, and alienation. The data are collected through close reading of the novel, emphasizing Kyuri’s dialogues, actions, and narrative development related to beauty practices. The findings reveal that K-beauty standards operate as a powerful ideological mechanism that shapes Kyuri’s perception of self-worth and social mobility, leading her to internalize the belief that physical transformation is necessary for success. This internalization results in multiple forms of alienation, including alienation from her body, identity, and social relationships, as her body becomes a commodity within a capitalist system. This study concludes that K-beauty standards function not only as cultural norms but also as instruments of capitalist control that reinforce social inequality and regulate individual identity